Studi tentang Kemampuan Teknik Dasar Bulutangkis Siswa Sekolah Dasar - Zarwan; Arsil; Sefri Hardiansyah (Majalah Ilmiah UPI YPTK, 2018)
The problem in this study is the low performance of badminton elementary school students in the Pembangunan Padang city which is likely due to the low basic technical skills of badminton. The purpose of this study was to know concretely about the basic technical skills of badminton owned by elementary school students in the Pembangunan Padang city. This type of research is classified into descriptive research. The population in this study were all students of elementary school students in the Pembangunan Padang city totaling 14 people, the entire population in this study was used as a sample. The instrument used to collect data in this study was to use basic technique tests to play badminton consisting of service, lob and smash. Analysis technique using descriptive statistical analysis. The results showed that: (1) Most elementary school students in Pembangunan Padang City had the ability to serve in the less category. (2) Most elementary school students in Pembangunan Padang City have the ability to lob in the less category. (3) Most elementary school students in Pembangunan Padang City have the ability to smash in good categories. (4) Most elementary school students in Pembangunan Padang City have basic badminton technical skills in the medium category.